Fatty Acids Composition of Red and Purple Pomegranate (Punica granatum L) Seed Oil - Hartati Soetjipto; Murda Pradipta; KH Timotius (Indonesian Journal of Cancer Chemoprevention, 2010)
The aim of this investigation was to determine the content and composition of fatty acid in seed oil of red and purple pomegranate (Punica granatum L). The extraction process was performed by Soxhlet extractor with petroleum ether as solvent. The separation and identification of pomegranate seed oil was done by using GCMS. The total oil content of red and purple  pomegranate  were 128 g/kg d.w  and 103 g/kg d.w respectively. Both showed the same major fatty acids  as palmitic, stearic, oleic, linoleic and  punisic acid. Oleic acid (19-21%) and linoleic acid (20-21%) were found as the most  dominant fatty acids in red pomegranate, whereas purple pomegranate seed oil was dominated by oleic acid (41-43%) and punicic acid  (0-25%). Neutral lipid  fraction of  red and purple pomegranate seed oils was more dominant than glycolipid and phospholipid. Neutral  lipid fraction  of red and purple pomegranate seed oil were  89 % and 91% respectively.  Glycolipid fraction  of red and purple pomegranate seed oil were 8 % and 5 %, whereas phosholipid fraction of red and purple pomegranate seed oil were 3 % and 4 %. The punicic acid content of  total lipid of  purple pomegranate seed oil (PPSO) (0-25%) was higher than red pomegranate (RPSO) (9-16%). On the contrary neutral lipid of red pomegranate showed higher punicic acid content (54-75%) than the purple pomegranate (14-55%). Glycolipid of red pomegranate contained  punicic acid  (0-42%). The punicic acid content  of the phospholipid fraction of  red pomegranate was higher (0-22 %) than the one of purple pomegranate (0-2%).Key words : fatty acid, pomegranate, Punica granatum, punicic acid, seed oil